Measurement of the CP asymmetry in B− → D− s D0 and B− → D−D0 decays; Journal of High Energy Physics; Vol. 2018, iss. 5 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen